Diseño de un sistema informático para la evaluación en tiempo real del criterio de producción académica mediante análisis de datos en el departamento de investigación de la UNACH - Andino Vaca, Francisco Javier (2025)
The objective of this project is to design an information system that automates the calculation of the Academic Production Index and its associated indicators at the university, a responsibility managed by the Research Department. The system leverages SQL functions and procedures to organize and process the database containing all academic production records of the institution. In addition, JavaScript-based frameworks are used to compute and display the index percentage in real time, allowing for an immediate assessment of whether the university meets the optimal value required for accreditation. The project began with a preliminary study of the Academic Production Index, its indicators, their calculation methods, and how the final value is determined. Subsequently, the system design process was carried out, including consultations with the Research Department at UNACH to obtain a backup of their database. PostgreSQL version 9 was chosen for data management, as it is the version currently in use at the institution. The database was filtered, SQL functions were developed to automate the calculations, and dynamic values were incorporated for specific indicators. Once the database was operational and its functions were validated by a research department expert—ensuring that the results were accurate and reliable—the database was deployed to the cloud. This enabled integration with a web application developed later, which provides a graphical and real-time visualization of the university’s Academic Production Index. The platform also allows users to adjust values for certain indicators and select specific years, especially useful during accreditation periods. Finally, a projection model was developed for the most recent year, using the system to determine the current value of the index and estimate which key indicators must be improved to reach the optimal annual target for accreditation.